المنهج الدلالي في فهم النص القرآني - زرال, صلاح الدين (Sciences humaines, 2014)
Searching to understand and interpret the Qur’an is one of the most important methodology tasks. The matter transcends a mere superficial understanding of the text, but goes to using the methodology mechanisms that help pave a sound understanding of the Qur’an text.  In this sense, Izutsu’s experience in understanding the Qur’an through the applied approach (the world’s insight or the world’s vision) will be used through his book (God and Men in the Qur’anic vision of the world). Izutsu has dealt with several key points in his semantic analysis and perhaps the most important thing in his methodology is his swift focus on the semantic issue of the approach’s beginnings and ends.    إن البحث عن المقاربة في فهم النص القرآني يعد من أهم البحوث المعاصرة ، بحيث تقوم هذه المقاربة على إجراءات وأدوات يتوصل من خلالها إلى فهم نظامي للنص لا مفرداتي ، وفي هذا السياق فقد استعانت المداخلة في ناحيتها التطبيقية بالتجربة الفريدة التي عرضها علينا الباحث الياباني إيزوتسو ، وهي تجربة تقوم على منهج دلالي سماه إيزوتسو برؤية العالم أو ما يسمى في عرف علم الدلالة بـ : نظرية الحقول الدلالية.